2013
DOI: 10.1186/2228-5326-3-42
|View full text |Cite
|
Sign up to set email alerts
|

Structural phase transformation and hysteresis behavior of Cu-Zn ferrites

Abstract: A series of Cu 1-x Zn x Fe 2 O 4 ferrite (with x = 0.0, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6) compositions were synthesized using the standard solid-state reaction technique. X-ray diffraction was used to study the structure of the above investigated samples. The theoretical and experimental lattice parameters (a th and a exp ) were calculated for each composition. A significant decrease in density and subsequent increase in porosity were observed with increasing Zn content. Curie temperature, T C , has been determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
12
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(16 citation statements)
references
References 44 publications
3
12
0
1
Order By: Relevance
“…Através do difratograma observou-se para a amostra isenta de chumbo (x = 0,00) que as fases são formadas exclusivamente pela fase ferrita com estrutura de espinélio com simetria cúbica (Ficha padrão JCPDS 01-077-0010) e para as amostras com estequiometria contendo x = 0,05 a x = 0,20 observou-se que as fases são formadas exclusivamente pela fase ferrita com estrutura de espinélio com simetria tetragonal (Ficha padrão JCPDS 34-0425). A transformação do espinélio cúbico para tetragonal é encontrado em concentrações de cobre com x = 0,00 para x = 0,30 [26]. No nosso caso, as amostras com estequiometria contendo x = 0,05 a x = 0,20 há indícios do efeito Jahn-Teller.…”
Section: Resultados E Discussõesunclassified
“…Através do difratograma observou-se para a amostra isenta de chumbo (x = 0,00) que as fases são formadas exclusivamente pela fase ferrita com estrutura de espinélio com simetria cúbica (Ficha padrão JCPDS 01-077-0010) e para as amostras com estequiometria contendo x = 0,05 a x = 0,20 observou-se que as fases são formadas exclusivamente pela fase ferrita com estrutura de espinélio com simetria tetragonal (Ficha padrão JCPDS 34-0425). A transformação do espinélio cúbico para tetragonal é encontrado em concentrações de cobre com x = 0,00 para x = 0,30 [26]. No nosso caso, as amostras com estequiometria contendo x = 0,05 a x = 0,20 há indícios do efeito Jahn-Teller.…”
Section: Resultados E Discussõesunclassified
“…The electrical conductivity of ZnxCu(1-x)Fe2O4 thin films sintered in oxygen was about 5% higher compared to thin films sintered in vacuum. This might be due to an increase in Fe 3+ and Cu + brought about by the presence of oxygen [21]. 6(a) shows the transmission spectra of ZnxCu(1-x)Fe2O4 thin films recorded in the 200 to 800 nm wavelength range.…”
Section: Electrical and Optical Analysismentioning
confidence: 99%
“…It is observed that the resistivity decreases with rising temperature while increases with Li 2 CO 3 contents. From the assumption of Verwey and De Boer, 23,24 it can be explained that the exchange of electrons between the ions of the same elements present in more than one valence state and are randomly distributed over crystallographic equivalent lattice cites. At the higher temperature, the respective ions which have impact upon the conduction mechanism are reduced.…”
Section: Resistivitymentioning
confidence: 99%